Prevalence of and Risk Factors for Community-Based Osteoporosis and Associated Fractures in Beijing: Study Protocol for a Cross-Sectional and Prospective Study - Sun, Menghua; Zhang, Yili; Shen, Hao; Sun, Kai; Qi, Baoyu; Yu, Chenchen; Zhi, Yingjie; Zhang, Ranxing; Jiang, Junjie; Chai, Yan; Wei, Xu; Xie, Yanming (Frontiers in Medicine, 2020)
Background: Osteoporosis (OP) patients are usually asymptomatic until osteoporotic fractures occur, which makes early diagnosis and prevention difficult, and the associated fractures secondary to OP could be highly preventable with appropriate management. Therefore, early identification and relevant evidence-based management of OP could guide the prevention of subsequent fractures. This study aims to investigate the prevalence of OP and the incidence of osteoporotic fractures in Beijing community residents to further explore the related risk factors and put forward some rational suggestions for people aged 45-80 years. Methods: This study will conduct an OP screening in the Beijing community and a prospective follow-up to investigate the incidence of osteoporotic fractures for at least two years. The study contents mainly include bone mineral density detection, biological sample collection, and questionnaire information collection. Discussion: The study will investigate the potential risk factors for and traditional Chinese medicine syndromes associated with osteoporosis based on large samples from the Beijing community. Additionally, the data for the two-year incidence of osteoporotic fractures among community dwellers in the Beijing area will be initially obtained. Registration: Chinese clinical trial registry, ChiCTR-SOC-17013090